The writing on the wall signs of faith against fascism - Martin, Eric (Cascade Books, 2023)
"How can people of faith connect their religious traditions with the rise of overtly fascist violence in the United States? That's the question this book takes up. With first-hand accounts from the largest white supremacist gathering in modern American history at Unite the Right in Charlottesville, Virginia, it shares how the clergy resisting Nazis and the KKK point a way forward for Christians in particular. But The Writing on the Wall expands outward to ask what churches can learn from antifascists, Black Lives Matter, and those working on the ground to combat the continuing coalition of far-right militias and gangs that promise to endure with or without Trump in office. In the wake of a deadly Capitol insurrection robed in Christian imagery, this book invites the faithful to imagine a counter-witness that does more than merely preach against hate. Using biblical exegesis, storytelling, interviews, thought experiments, art, and theology, The Writing on the Wall explores how we can rethink notions of civil disobedience, nonviolence, love, prayer, and liturgy to enflesh a worthy faith in the face of a fascist creep." --
Keywords: Katholische Kirche; Gewalt; Faschismus; Widerstand; USA; Christianity and politics / Catholic Church; Government, Resistance to / Religious aspects / Catholic Church; Unite the Right Rally, Charlottesville, Va., 2017; Social change / Religious aspects / Christianity; Christian sociology; Résistance au gouvernement / Aspect religieux / Église catholique; Virginia / Charlottesville; 2017